If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 66 = 7x + -34 Reorder the terms: 66 + 2x = 7x + -34 Reorder the terms: 66 + 2x = -34 + 7x Solving 66 + 2x = -34 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 66 + 2x + -7x = -34 + 7x + -7x Combine like terms: 2x + -7x = -5x 66 + -5x = -34 + 7x + -7x Combine like terms: 7x + -7x = 0 66 + -5x = -34 + 0 66 + -5x = -34 Add '-66' to each side of the equation. 66 + -66 + -5x = -34 + -66 Combine like terms: 66 + -66 = 0 0 + -5x = -34 + -66 -5x = -34 + -66 Combine like terms: -34 + -66 = -100 -5x = -100 Divide each side by '-5'. x = 20 Simplifying x = 20
| 7x+169=5x+153 | | (6x+14)+11= | | -14+10x=9x+23 | | (6x*14)+11= | | 3(x+4)+15=36 | | 8(9+3x)+11= | | 4q/5+6=18 | | (5x-9)+9= | | 4q/5+6=188 | | y=(2e^2t)+4 | | -6v-6=-3(v+6) | | 4x^2-29+x^2-15+x^2+8=180 | | (18x+13)-7x= | | 2.5w-1,3w=14.4 | | 8x-1=6x+9 | | (x+7)=15 | | 3(x-5)+14(x+6)= | | 4(3x+12)+14x-13= | | 8(u+6)=-5u-17 | | 2.5w-1.3w=14.4 | | 9x+4+4x-5=90 | | (5x+12)+(8x-5)= | | 9v-43=2(v+3) | | w/15.36=6 | | (x-4)=13 | | -7x-87=-14x+39 | | 18x=48+12x | | -4*-4*-4=x | | 5x-10+2x+9=90 | | 4x1/12 | | 14.3-.4x=2.6+5.6 | | 5+2(3t-7)=3(2t+5)-24 |